Applications classification and scheduling on heterogeneous hpc systems using experimental research - Xia, Y.; Zhu, M.; Kuang, L.; Ma, X. (Journal of Digital Information Management, 2011)
Heterogeneous high-performance computing (HPC) systems have been proposed as a power efficient alternative to traditional homogeneous systems. In heterogeneous HPC system, fast CPUs which have complex pipelines, high clock frequencies as well as high power consumption are combined with slow ones which have simple pipelines, low clock frequencies as well as low power consumption. Different types of applications should be distributed to run on different type of CPUs, in order to achieve a trade-off between energy and performance. In this paper, we use experimental research to investigate the applications classifications which categorize each application as the CPU-intensive, memory-intensive, or phase-change application. We also conduct some experiments to measure the current, power, and energy of different types of applications. Afterwards, a scheduling method for applications on heterogeneous HPC systems is proposed. The experiment shows that the scheduling method can trade off the latency and energy consumption based on the applications classification and measurement.
Keywords: Applications Classification; Heterogeneous Systems; High Performance Computing; Scheduling

Reasoning on context satisfiability for service recommendation in mobilenetwork - Kuang, L.; Chen, L.; Xia, Y. (Journal of Digital Information Management, 2011)
The Ubiquitous Computing envisions a world of communicating mobile devices. As mobile devices usually have limited resources, it brings up the challenge to search and invoke services at any time and any place in an accurate, efficient and adaptive way. In this paper, we propose to filter services by matchmaking the precondition of service invocation and the context information of service consumer, in order to increase the accuracy and adaptivity of service discovery and recommendation in mobile environment. We construct context ontology to describe the environment when a service consumer submits service request first. And then, we propose to formalize the precondition of a successful service invocation based on a lightweight DL theory. Finally, reasoning on context satisfiability can be used for service recommendation. A case study shows our approach works well.
Keywords: Context Satisfiability; Precondition Formalization; Service Reasoning; Service Recommendation